Answer:
x=133 y=-25
Step-by-step explanation:
I'll do both ways for you. So let's start with Substitution:
With the sub method, you have to set both equations equal to each other by setting them equal to the same variable. Since there is no coefficient in front of both x's in both equations, that variable will be easiest to solve for.
x + 2y = 83 & x + 5y = 8
Solve for x.
x = 83 - 2y & x = 8 - 5y
Once you have solved for x, set each equation equal to one another and solve for y now.
83 - 2y = 8 - 5y
Isolate all variables to one side:
83 = 8 - 3y
Now subtract the 8 to fully isolate the y variable:
75 = -3y
Divide by -3:
-25 = y Now that you have your first variable, plug it into one of the original equations and solve for x.
x + 2(-25) = 83
x - 50 = 83
x = 133
Now for the Elimination method. For this method you need to get rid of a variable by either subtracting/adding each equation together. Again, since you can subtract and x from both equations, you will be left with only the y variable to solve:
Put each equation on top of one another and subtract:
x + 2y = 83
- (x + 5y = 8)
The x's will cancel out:
(x - x) + (2y - 5y) = (83 - 8)
Simplify:
-3y = 75
Solve for y
y = -25
Then, plug y = -25 into one of the original equations:
x + 5(-25) = 8
Solve for x:
x - 125 = 8
x = 133
Hope this helps!
Step-by-step explanation:
We can prove the statement is false by proof of contradiction:
We know that cos0° = 1 and cos90° = 0.
Let A = 0° and B = 90°.
Left-Hand Side:
cos(A + B) = cos(0° + 90°) = cos90° = 0.
Right-Hand Side:
cos(A) + cos(B) = cos(0°) + cos(90°)
= 1 + 0 = 1.
Since LHS =/= RHS, by proof of contradiction,
the statement is false.
Answer:
- Right Angle Triangle – A Right triangle is a triangle in which one angle is a right angle (that is, a 90-degree angle). The relation between the sides and angles of a right triangle is the basis for trigonometry (opposite, hypotenuse, adjacent).
- Obtuse Triangle – An obtuse triangle is a triangle with one obtuse angle (greater than 90°) and two acute angles.
- Acute Triangle – An acute triangle is a triangle with three acute angles (less than 90°).
12 - Right Angle Triangle
13 - Obtuse Triangle
14 - Acute Triangle
15 - Acute Triangle
16 - Right Angle Triangle
17 - Obtuse Triangle
The answer would be 317d or you could
do 317(d)
4b because you distribute the 4 to get 8b - 4b so that equals 4b